Pelatihan Penyusunan Media Pembelajaran untuk Mahasiswa Peserta PLP PGSD FKIP Universitas Mataram - Heri Setiawan; Lalu Sirajul Hadi; Nanda Mustika Meilan; Catur Prima Eka Putra Abdullah; Irwandi Putra Ramli (Dedikasi Cendekia: Warta Pengabdian Pendidikan, 2025)
This community service program aims to enhance the ability of PGSD students at the Faculty of Teacher Training and Education, University of Mataram, in developing instructional media as preparation for the School Field Introduction Program (PLP). Previous evaluations indicate that students still rely on conventional media such as chalkboards and printed images, which lack innovation and are not designed based on instructional principles. In fact, instructional media play an essential role in helping elementary students understand abstract concepts, increasing learning motivation, and creating engaging and meaningful learning experiences. Through the workshop, students gained knowledge about media concepts and types, characteristics of elementary learners, and criteria for selecting appropriate instructional media. The activity continued with guided practice in conducting needs analysis, designing, and presenting their media products. The results show improved student competence in producing creative, functional, and pedagogically relevant media, making them better prepared for PLP implementation in elementary schools.